Fuzzy Implicative Ideals in KU-algebras - Samy Mohammed Mostafa; Ola Wageeh Abd El-baseer (Journal of New Theory)
In this paper, we consider KU-implicative ideal (brieflyimplicative ideal) in KU-algebras. The notion of fuzzy implicative ideals in KU-algebrasare introduced, several appropriate examples are provided and their someproperties are investigated. The image and the inverse image of fuzzyimplicative ideals in KU-algebras are defined and how the image and the inverseimage of fuzzy implicativeideals in KU-algebras become fuzzy implicative ideals are studied. Moreover,the Cartesian product of fuzzy implicative ideals in Cartesian product of KU-algebrasare given.